Pure Profit Rates and Tobin's q in Nine OECD Countries - Chan-Lee, James H.. (OECD Publishing, 1986)
This paper extends a previous study of profit trends to consider valuation ratios (Tobin's q) in nine countries. Tobin's q embodies market expectations and is an indicator of expected pure profit rates on the existing capital stock. Since 1982, equity markets have recovered substantially. By end-1985, values of Tobin's q were close to their 1974 levels and close to the symbolic figure of unity. The theoretical and conceptual relevance of q is considered, as well as data and measurement limitations. Real debt and equity costs of finance are considered in the light of buoyant stock markets. The implications of the strong recent recovery in q for investment are also noted ...
Keywords: Economics